Student Facilitator and Explaining Model and Mathematical Communication Ability in Distance Learning - Intan Isma Fauziyah; Wardani Rahayu; Siti Rohmah Rohimah (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
Communication is one of the important skills that need to be grown and improved in learning mathematics. Improving mathematical communication ability can be carried out through the application of learning models in which there are discussion activities between students and teachers, one of which is the Student Facilitator and Explaining model. This study aims to determine whether the Student Facilitator and Explaining model in distance learning has an effect on mathematical communication ability. The experimental design used is a quasi-experimental type of posttest-only control group design with a sampling technique using cluster random sampling. The research instrument used a mathematical communication ability test on the quadrilaterals and triangles material, totaling 5 questions which had been tested for validity and reliability. The results showed that the Student Facilitator and Explaining model in distance learning has a significant effect on students' mathematical communication ability by 79%. Keywords: Student Facilitator and Explaining Model, Distance Learning, Mathematical Communication Ability.